(untitled) (Vietnam Journal of Community Medicine, 2022)
Rationale: Metabolic syndrome (MetS) has been a public health issue in the spotlight recently. The metabolic syndrome is increasing in the big cities and the red river delta provinces such as Thai Binh, where there is an incremental prevalence of MetS. Therefore, it is necessary to identify the situation of MetS engagement and its relevant factors. Research objective: Identifying some factors relating to metabolic syndrome in people aged 25 to 64 in Thai Binh province. Research objects and methodology: The cross-sectional study was conducted on 1336 people aged 25-64 years, aiming to identify the factors related to Metabolic Syndrome in people aged 25-64 in 6 districts in Thai Binh province in 2019. Results: Some factors related to the Prevalence of Metabolic syndrome include: increase with age (OR = 1.08, p<0.05); BMI (OR = 1.45, p<0.05); heart rate (OR = 1.05, p<0.05); frequent use salty sauce (OR = 2.40, p<0.05); regularly add salt to food (OR = 2.88, p<0,05); history of diabetes (OR = 2.85, p<0.05); reduced fat diet (OR = 1.34, p<0.05). Conclusion: Metabolic syndrome was related to age, BMI, heart rate, salty diets, diabetes and lowfat diets.